2002
DOI: 10.1099/00221287-148-7-2019
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the role of charged residues in target-cell binding, potency and specificity of the pediocin-like bacteriocin sakacin P

Abstract: The significance of charged residues for the target-cell binding, potency and specificity of pediocin-like bacteriocins has been studied by site-directed mutagenesis of sakacin P. Most of the charged residues are located in the N-terminal half, which is thought to mediate the initial binding of these bacteriocins to target cells through electrostatic interaction. All the mutated peptides in which the net positive charge was reduced by one (by replacing a charged residue with threonine) exhibited reduced bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
69
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 46 publications
7
69
0
1
Order By: Relevance
“…Its helix content would be sufficient to account for both its low biological activity and the emission shift in fluorescence. The G13E substitution introduces a negative charge in the positive segment of the N-terminal half of the bacteriocins that is proposed to be involved in the primary binding of the peptide to the membrane (8,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its helix content would be sufficient to account for both its low biological activity and the emission shift in fluorescence. The G13E substitution introduces a negative charge in the positive segment of the N-terminal half of the bacteriocins that is proposed to be involved in the primary binding of the peptide to the membrane (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally observed that mutations are deleterious for bactericidal activity, but in some cases, they reinforce the antagonist potency (18,34,41). All these "enhancing" substitutions involve an increase in the net positive charge, H12K, T20K, and 44K in sakacin P (34). Binding of pediocin PA-1, studied by tryptophan fluorescence (7), showed that the K11L-H12L derivative bound weakly to the lipid vesicles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These two domains are separated by a flexible hinge that enables the two domains to move relative to each other. The N-terminal domain binds to the target cell surface (10,11), whereas the more hydrophobic C-terminal domain enters the hydrophobic part of the cell membrane (3,12,13). Despite their extensive sequence similarity, the pediocin-like bacteriocins differ markedly with respect to the bacteria they kill (6,14).…”
mentioning
confidence: 99%
“…Much effort has been devoted to the subclass IIA of bacteriocins to determine the structureefunction relationships. Though variants generated in these types of studies are useful from an academic standpoint, none of them display increased activity against several microorganisms (Kazazic, Nissen-Meyer, & Fimland, 2002).…”
Section: Biotechnological Applicationsmentioning
confidence: 99%